República, liberdade e educação em Thomas Jefferson - Machado, Denise de Almeida (Universidade Federal de São Carlos, 2020)
This study deals with the resumption of the philosophical and political principles that support the notion of education, freedom and republic, according to the perspective of author Thomas Jefferson. The central objective is to understand the philosophical elaboration of the republican conception in the context of the Philosophy of Lights, having as a research scenario the revolutionary conjuncture of the United States at the end of the 18th century. At this time, outbreaks address pioneering policies and education, which link the narrow way to republican philosophy with the purposes of educational policies and institutions. For Jefferson, this state must offer all the necessary conditions to live in conditions of freedom and freedom. An investigation examined in a literature review, with a hermeneutic, argumentative and interpretative effort, with the perspective of approaching the Jeffersonian philosophical-political approach on education, freedom and republic with originality, since there is an insufficiency of studies of this nature is already being used. In addition, proceed to document analysis of epistolary texts and other primary sources. Finally, conclude if the republican system needs to be free of political and religious interests that create obstacles to the implementation of the principles of freedom, education and the Republic itself.
Republic, freedom and education in Thomas Jefferson
Keywords: Educação republicana; Liberdade republicana; Iluminismo e Thomas Jefferson; Independência americana; República e Thomas Jefferson; Republican education; Republican freedom; Enlightenment and Thomas Jefferson; American Independence; Republican and Thomas Jefferson; CIENCIAS HUMANAS::EDUCACAO